(untitled) (The Pretoria Student Law Review, 2021)
Through this paper, I aim to disprove the claim that knowledge, academic thought and societal discourse are neutral and objective, as well as explore links between transformation of the university system, the teaching of law and society in general. I argue that the constitution has failed at achieving a ‘free, equal and unified’ South Africa despite its objectives, and that the examination of the law with a critical approach of its racially charged aspects will offer some insight into addressing deep colonial biases.12 This will be done through examining the various arguments surrounding Eurocentrism and white supremacy in academia, society and the law.13